2021
DOI: 10.3390/forecast3020017
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Endgame Simulation Modelling: Assessing the Impact of Policy Changes on Smoking Prevalence in 2035

Abstract: Smoking causes substantial amount of mortality and morbidity. This article presents the findings from simulation models that projected the impact of five potential Tobacco Endgame strategies on smoking prevalence in Ontario by 2035 and expected impact of smoking prevalence “less than 5 by 35” on tax revenue. We used Ontario SimSmoke simulation for modelling the expected impact of four strategies: plain packaging, free cessation services, decreasing the number of tobacco outlets, and increasing tobacco taxes. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Seven simulation modelling studies examined the potential impacts of tobacco tax increases within the context of an endgame strategy. The four modelling studies that estimated health outcomes all concluded that tax increases would result in notable population health improvements,55 59 60 62 and the four that reported changes in smoked tobacco use all estimated significant decreases in prevalence,55 60 63 64 thus demonstrating the policy could contribute to an endgame. However, the only synthesis (a modelling study) that demonstrated how a tobacco endgame could be achieved solely through raising taxes showed they would need to increase by more than 20% (above inflation) annually,64 a figure notably higher than Australia’s 12.5% annual tax increases between 2017 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven simulation modelling studies examined the potential impacts of tobacco tax increases within the context of an endgame strategy. The four modelling studies that estimated health outcomes all concluded that tax increases would result in notable population health improvements,55 59 60 62 and the four that reported changes in smoked tobacco use all estimated significant decreases in prevalence,55 60 63 64 thus demonstrating the policy could contribute to an endgame. However, the only synthesis (a modelling study) that demonstrated how a tobacco endgame could be achieved solely through raising taxes showed they would need to increase by more than 20% (above inflation) annually,64 a figure notably higher than Australia’s 12.5% annual tax increases between 2017 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…The four modelling studies that estimated health outcomes all concluded that tax increases would result in notable population health improvements,55 59 60 62 and the four that reported changes in smoked tobacco use all estimated significant decreases in prevalence,55 60 63 64 thus demonstrating the policy could contribute to an endgame. However, the only synthesis (a modelling study) that demonstrated how a tobacco endgame could be achieved solely through raising taxes showed they would need to increase by more than 20% (above inflation) annually,64 a figure notably higher than Australia’s 12.5% annual tax increases between 2017 and 2020. One synthesis concluded the policy would result in sizeable decreases in health inequalities between Māori and non-Māori people in NZ,62 and two noted decreased health system costs 60 62.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of and effective fiscal policy for the smoking control in the health context begins understanding the smoking impact over the health market equilibrium. The characteristics and the magnitude of this impact determine the particular characteristics from the appropriate fiscal policy for the smoking control [6].…”
Section: Introductionmentioning
confidence: 99%